Advancing the Study of “Goals of Best Practice”: Toward Achieving Optimal Best – Educational Implications to Developments in Flow Research and Positive Optimal Psychology - Phan, Huy P.; Ngu, Bing Hiong (Frontiers in Psychology, 2022)
The paradigm of positive psychology is significant, introducing positive psychological concepts such as ‘flourishing’, ‘optimal best’, and ‘a state of flow’. In terms of research development of positive psychology, we have made extensive theoretical, empirical, and methodological contributions by advancing the study of optimal best. One aspect of this research, notably, consists of advancement of the psychological process of optimization. Optimization, in brief, provides a theoretical account into the ‘optimization’ of a person’s state of functioning. For example, non-academically, a senior citizen’s seeking to successfully achieve an optimal state in Buddhist meditation would require some form of optimization. Recent research development has, interestingly, considered a related concept known as ‘goals of best practice’ (i.e., GsBP)(Phan, Ngu et al. In Press), which may co-exist with the process of optimization and/or assist to account for the optimization of learning experiences. This conceptual analysis article utilizes the paradigm of philosophical psychology to advance the study of optimal best by focusing on three major aspects: (i) to consider conceptually and philosophically how and/or the extent to which goals of best practice could, in fact, relate to the nature of flow, flourishing, and optimal best, (ii) to consider a methodological account, which could help to measure and assess the concept GsBP, and (iii) to consider the potential practicality of GsBP in educational contexts, for example, which may assist to facilitate and motivate the achievement of optimal best.